Electronic structure, structural properties, and dielectric functions of IV-VI semiconductors: PbSe and PbTe - Albanesi, Eduardo Aldo (2000)
The electronic structure and frequency dependent dielectric function E(E) of rocksalt semiconductors PbSe and PbTe are investigated using the local density approximation (LDA) and the generalized gradient approximation as two different exchange and correlation approximations, within the full-potential linearized augmented plane-wave approach. Spin-orbit coupling has been incorporated in the study. The results are presented and compared with other recent calculations and experimental data. Structural properties are also obtained by means of calculations of total energy as a function of lattice parameters. The bulk structural parameters are sensitive to the choice of exchange and correlation approximation. The essential features of the band structure and density of states of PbSe and PbTe are reproduced by our calculations and agree quite well with available experimental results. The position of the minimum energy gap is correctly predicted, although the value of the gap is as usual, underestimated by the local density approximation with respect to the experimental data. This gap value is improved by the inclusion of the generalized gradient approximation. Also, we have calculated the real [E1(W)] and imaginary [E2(W)] parts of E(W) for both compounds, in the framework of the LDA scheme for exchange and correlation. The inclusion of spin-orbit coupling leads to a richer structure in both E1(W) and E2(W). The agreement with experimental results is satisfactory.